2016
DOI: 10.5851/kosfa.2016.36.6.791
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an Antioxidant Protein from Fertilized Eggs

Abstract: Free radicals may attack cells or tissue, leading to chronic diseases, and antioxidant consumption is potentially useful for removing free radicals. Egg proteins may be used as potential sources of antioxidant considering their ability of scavenging free radicals to apply for food or cosmetics industry. In this study, we obtained a natural antioxidant protein from fertilized eggs, which was a dietary supplement in some Asian countries. Meanwhile, antioxidant activities of these proteins were evaluated using di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They have been shown for its biological activities, including anti-fatigue, antioxidant activity and improving immunity 11 . In addition, as natural dietary supplement, chick embryo eggs are considered as the nutrition, have quality supplement and illness treatment in China 12 . Studies have shown that chick embryo contains stem cell factor (SCF), nerve growth factor (NGF), epidermal growth factor (EGF), interleukin-4 (IL-4) and interleukin-2 (IL-2) 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown for its biological activities, including anti-fatigue, antioxidant activity and improving immunity 11 . In addition, as natural dietary supplement, chick embryo eggs are considered as the nutrition, have quality supplement and illness treatment in China 12 . Studies have shown that chick embryo contains stem cell factor (SCF), nerve growth factor (NGF), epidermal growth factor (EGF), interleukin-4 (IL-4) and interleukin-2 (IL-2) 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“… Abeyrathne et al (2014) showed that peptide derived from ovalbumin were hydrolyzed by alcalase and trypsin showed strong iron- and copper-binding capacities and antioxidant capacity. The sequence of antioxidant protein obtained from fertilized eggs on day 15 exhibited highly similar to ovalbumin ( Yang et al , 2016 ). Thus, we suspected that the purified protein in this study was a new antioxidant protein.…”
Section: Discussionmentioning
confidence: 99%
“…Chicken embryo eggs are regarded as a high-quality natural nutrition supplement and sickness cure in China (where they are known as Mao Dan) and other Southeast Asian nations [1]. Pregnant women, the elderly and even cancer patients are advised to consume it [2].…”
Section: Introductionmentioning
confidence: 99%